Establishment of a Pseudomonas aeruginosa Biofilm Model Using a Drip Flow Reactor: Evaluation of Antibiotic Efficacy against Biofilm Formation and Destruction - Minh Trong Quang; Duong Hai Thi Vo; Minh Thai Nguyen (Biomedical and Biotechnology Research Journal)
Background: Pseudomonas aeruginosa (PA) is a significant cause of nosocomial infections, particularly because its ability to form biofilms on medical devices complicates treatment. This study developed a biofilm model using a drip flow reactor (DFR) system and apply it to investigate the effects of antibiotics on biofilm formation. Methods: The biofilm-forming capacity of PA strains ATCC 9027, ATCC 27853, and PA 01 (a PA isolate from wastewater samples) was evaluated using a DFR system. This model was then used to assess biofilm resistance to antibiotics through flow cytometry analysis. Results: A PA biofilm model was successfully established in the DFR system, as evidenced by images of the carrier and flow cytometry analysis results. Significant differences in biofilm formation were observed among the tested strains (one-way ANOVA, P < 0.01). The timing of antibiotic administration was found to influence biofilm formation. The combination of colistin and rifampicin exerted a synergistic effect, significantly enhancing both the inhibition of biofilm formation and the destruction of existing biofilms compared with individual antibiotic treatments (one-way ANOVA, P < 0.01). Conclusion: This study successfully developed a PA biofilm model using the DFR system and applied it to evaluate the efficacy of colistin and rifampicin, both individually and in combination, against PA biofilms. The DFR model, coupled with flow cytometry analysis, is a valuable tool for investigating biofilm formation kinetics and assessing the impact of antibiotics on biofilm development and eradication.